Maintaining postharvest quality of the tomato fruit by employing methyl jasmonate and ethanol vapor treatment - Tzortzakis, Nikos G.; Economakis, Costas D. (My University, 2007)
The postharvest quality of tomato fruit (Lycopersicon esculentum L.) was evaluated after treatment with natural volatile compounds (methyl jasmonate [MJ] or ethanol) and storage at 13C during or following vapor exposure. The fruit treated with natural volatiles did not differ on fruit decay during vapor exposure, but following exposure and transfer to ambient air, the fruit had less decay at storage temperature. Volatile-treated fruit tended to maintain firmness during exposure, and the effects were significant for ethanol-treated fruit, following storage to ambient air. Sugar (i.e., fructose and glucose) concentration was stimulated in ethanol-treated fruit following exposure and transfer to ambient air. Ascorbic acid concentration was stimulated in MJ-treated fruit during exposure and persisted (including ethanol treatment) following transfer to ambient air. Total phenolics declined during vapor exposure and increased for MJ-treated fruit after transfer to ambient air. Lycopene concentration did not differ during MJ exposure but increased following volatile exposure. The fruit samples treated with vapors had accelerated percentage weight loss compared with untreated fruit during ripening but without commercial interest, whereas citric acid content did not differ among the treatments. The results suggest that MJ and ethanol vapor may improve fruit quality-related attributes on top of the well-documented antimicrobial protection during fresh produce storage and transit. The data presented in this work suggest that the use of natural volatiles is an innovative and useful tool as an alternative to the use of synthetic fungicides or other sanitation techniques in storage/packaging. Vapor enrichment may reduce disease development with a major contribution to limiting the spread of the pathogen by lowering the spore load (spore production) in the storage/transit atmospheres as well as the use of natural volatiles as an alternative food preservative. In addition to these, the improvement of fruit quality observed in the present work is of great market importance. The effects of natural compounds on individual microorganisms (fungi and bacteria), both responsible for spoilage and foodborne pathogens, as well as the minimum concentration to gain effectiveness without affecting fresh produce quality and storage deserve further research. © 2007, Blackwell Publishing.
Keywords: Methyl jasmonate; Fruit; Jasmonate MeJA